A dinâmica entre raízes e asas: um estudo sobre organizações inovadoras - Aguiar, Silvana Marques dos Santos Pereira de (2004)
The present work studies organization innovation under the perspective of culture dynamics based on the culture dynamic concepts following American Professor Mary Jo Hatch. Such perspective seems to facilitate the understanding of both subjective and objective organization innovation through the four processes proposed by the model: manifestation, realization, symbolization, and interpretation. Innovation may be included in those four processes in the following way: it is modeled under the influences of cultural assumptions and values, it is turned into material reality as artifact, which in its turn is symbolized and interpreted in tune with assumptions and values, thus closing a cycle. The dynamic process was the object of field research at three organizations considered innovative. The methodology used was grounded research. The aim was to identify factors that were present at organizations under systematic innovation, as well as the inter-relation between and among those factors. A metaphor was created – “roots and wings” – to picture the scenario found at organizations under study: basic, amalgamation factors – “roots”, as well as mobility factors – “wings”.